2010
DOI: 10.1038/ijo.2010.105
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-α2-glycoprotein: an adipokine modulator of body fat mass?

Abstract: The importance of white adipose tissue in the control of energy balance is now firmly recognized. In addition to fuel storage, adipocytes secrete an array of proteins factors (adipokines), which regulate multiple physiological and metabolic processes as well as influence body fat accumulation. Zinc-a2-glycoprotein (ZAG), a lipid mobilizing factor initially characterized as a tumor product associated with cachexia, has recently been identified as a novel adipokine. Although the exact role of ZAG in adipose tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 67 publications
2
64
1
4
Order By: Relevance
“…Further analysis found the subjects with GG genotype have much higher body weight, BMI, waist circumference and SBP in comparison with the subjects with AA genotype. All of these findings together with our previous in vivo studies (Bing et al, 2010;Gong et al, 2009;Gong et al, 2010), which demonstrated serum ZAG level is negatively correlated with body weight, BMI, fat mass and waist circumference, and that administration of high-fat-diet induced obese mice with ZAG would result in a great reduction in body weight and body fat, imply that ZAG is an important regulatory factor of body weight and plays a crucial role during the occurrence and development of obesity (Bing et al, 2010). About the gender specific association in rs4215 site in the ZAG gene with obesity, one possible explanation is as follows.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Further analysis found the subjects with GG genotype have much higher body weight, BMI, waist circumference and SBP in comparison with the subjects with AA genotype. All of these findings together with our previous in vivo studies (Bing et al, 2010;Gong et al, 2009;Gong et al, 2010), which demonstrated serum ZAG level is negatively correlated with body weight, BMI, fat mass and waist circumference, and that administration of high-fat-diet induced obese mice with ZAG would result in a great reduction in body weight and body fat, imply that ZAG is an important regulatory factor of body weight and plays a crucial role during the occurrence and development of obesity (Bing et al, 2010). About the gender specific association in rs4215 site in the ZAG gene with obesity, one possible explanation is as follows.…”
Section: Discussionsupporting
confidence: 79%
“…Although the pathogenesis of obesity and its associated co-morbidities are multifactorial, growing evidence suggests that altered production of adipose-derived protein factors (adipocytokines), such as leptin, adiponectin and tumor necrosis factor-α (TNF-α), plays an important role in the occurrence and development of obesity (Bing et al, 2010). ZAG has been identified recently as such a novel adipokine due to its close link to lipid, glucose metabolism, its crucial role in regulation of body weight and fat mass, as well as its significant antiobesity and antidiabetic effects in rat and ob/ob mice Tisdale, 2010b, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…ZAG is involved in lipid mobilization (14). It is elevated in urine during energy-demanding conditions (15), but decreases in acute kidney injury (16).…”
Section: Discussionmentioning
confidence: 99%
“…Here we demonstrate the association between the level of endogenous Zn 2+ (but not other microelements) and bovine ovarian functions: BCS2 cows had higher blood Zn 2+ levels, lower ovarian, follicular and corpora albicantia size in comparison with the BCS3 animals, while granulosa cells isolated from the ovaries of the former released more oestradiol than those obtained from the BCS3 group. Zn 2+ has been shown to be stimulator of appetite (Suzuki et al, 2011) and adipose tissue development (Bing et al, 2010). Therefore, an increased plasma Zn 2+ level in cows with a tendency towards emaciation might be a promoter of bovine appetite, fat gain, and return to average BCS.…”
Section: Discussionmentioning
confidence: 99%